If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 = 3x + 1 Reorder the terms: -35 = 1 + 3x Solving -35 = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -35 + -3x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -35 + -3x = 1 + 0 -35 + -3x = 1 Add '35' to each side of the equation. -35 + 35 + -3x = 1 + 35 Combine like terms: -35 + 35 = 0 0 + -3x = 1 + 35 -3x = 1 + 35 Combine like terms: 1 + 35 = 36 -3x = 36 Divide each side by '-3'. x = -12 Simplifying x = -12
| 8x-1=8x-3 | | 250=25(x+7) | | -45-5=3b+9 | | -3d+5-9d=18 | | -4=a+4-5 | | 6x-18=x^2-18 | | 8x+4(-2x+6)=254 | | 25=-3+2(k-8) | | 2i^8-5i^14= | | 129=4r+3(3r-9) | | -18=4r-9r | | .72=.4(x+1.4) | | 5(-5+5w)+(7v+9)1= | | 3a=135 | | 13.99(c-12)=1000 | | 29=33.52+a(10.80) | | 14+2x+5x-1=180 | | 9(9y-5)-(6y+8)= | | [x-8]-9=-5 | | 13.99(c-12)=97.93 | | 0=7f+4(5-3f) | | -7.2(2-y)-5.1y+4.1= | | 12(4x+1)=108 | | [4x+12]=4 | | 2x+14=40 | | 4(2h+3)=8h-3 | | 2-2=x+64 | | 2-7x-8=-13 | | 20x^4-5x^2=0 | | -sin(16x)=0 | | 828b*-22=18 | | 3x-5(x-2)=-6+5x-26 |